Survey on Public Awareness On AIDS- Role Of Government And Non Government Agencies In A Rural South Indian Community - Balagnesh G; Chandrasekar V; Sai T S R; Babu Sudhakar V (Wolters Kluwer Medknow Publications, 1996)
Research Question: What is the level of Public awareness on AIDS in a rural community and to what extent the government and non-government agencies have played their role in creating the awareness? Objectives: (i) To study the public awareness on AIDS in a rural community (ii) To Study role of government and non-government agencies in creating the awareness on AIDS. Design: Cross-sectional study Setting: Rural area under S. V. Medical College Triputi (AP) Participants: 100 males (15-45 yrs) and 100 females (15-45 yrs). Study variables: Awareness on AIDS, Government and non-government agencies. Statistical Analysis: Percentages Results: Most of the persons interviewed had minimal knowledge on AIDS. Quite a large section of the â€˜ study population was ignorant over the safety offered by condoms in preventing AIDS. Doordarshan and Newspaper agencies played much role in creation the awareness on AIDS, while the non-government agencies like Lionsâ€ Club, Rotary Club. Indian Junior Chamber etc. played no role in creating the awareness on AIDS in the study area. Recommendations: Government health sector should take more responsibility in educating the people and creating adequate awareness on AIDS. Non-government agencies should involve themselves in creating awareness on AIDS.